Lack of Association between Interleukin-10 Gene Polymorphisms and Graft Rejection Risk in Kidney Transplantation Recipients: A Meta-Analysis. - Jiachuan Xiong; Yiqin Wang; Ying Zhang; Ling Nie; Daihong Wang; Yunjian Huang; Bing Feng; Jingbo Zhang; Jinghong Zhao (PLoS ONE, 2015)
Interleukin-10 (IL-10) is an important immunomodulatory cytokine. Several studies focused the association between IL-10 promoter gene polymorphisms and graft rejection risk in kidney transplantation recipients. However, the results of these studies remain inconclusive. The aim of this study was to conduct a meta-analysis to further assess the associations.The PubMed, Embase, and Ovid Medline databases were searched. Two independent authors extracted data, and the effects were estimated from an odds ratio (OR) with 95% confidence intervals (CIs). Subgroup and sensitivity analyses identified sources of heterogeneity.A total of 16 studies including 595 rejection patients and 1239 stable graft patients were included in order to study the IL-10 -1082 (rs1800896 G/A), -819 (rs1800871 C/T), -592 (rs1800872 C/A) and IL-10 (-1082,-819,-592) polymorphisms. The -1082 G/A polymorphism was not associated with an increased graft rejection risk (OR = 1.03; 95%CI, 0.85-1.25, P = 0.74 for GA+AA vs. GG model). Moreover, all of the -819 C/T (OR = 1.06, 95%CI, 0.79-1.42, P = 0.70 for TA+TT vs. CC model), -592 C/A (OR = 1.10, 95% CI, 0.85-1.42, P = 0.47 for AC+AA vs. CC model) and IL-10 (-1082,-819,-592) polymorphisms (OR = 1.00, 95%CI, 0.79-1.27, P = 0.98 for I+L vs. H model) did not increase the graft rejection risk. In addition, we also performed subgroup analysis by ethnic group (mainly in Europeans or Asians) and rejection type (acute or chronic). There was also lack of evidence of a significant association between the IL-10 gene polymorphism and graft rejection risk. The present meta-analysis indicated that the IL-10 gene polymorphism was not associated with graft rejection risk in kidney transplantation recipients.This meta-analysis found evidence that the IL-10 polymorphism does not increase the risk of graft rejection in kidney transplantation recipients. Further chronic rejection and other ethnic population studies are needed to confirm our results.